PERTANGGUNGJAWABAN IMPORTIR ATAS KERUGIAN EKSPORTIR AKIBAT DARI FREE ON BOARD TRAP - Paramitha Sasongko, Angela; Pujawan, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
In international trade transactions may arise a dispute that could develop into a legal dispute. This can cause unwanted loss of the parties, whereas the likelihood of disputes in international trade is very large because of the delivery and receipt of goods often carried out in different countries. One category is a condition Free On Board (FOB). This paper describes whether the importer is responsible for the losses incurred by exporters in case of FOB Trap. In addition, this paper also describes what legal steps can be taken by exporters for losses suffered due to FOB Trap.
Keywords: Accountability, Importers Exporters, Free On Board Trap